Women’s Lived Experiences of Reproductive Coercion and Abuse - Wellington, Molly (Journal of family violence, 2025)
PurposeReproductive coercion and abuse (RCA) refers to the use of physical, psychological or sexual violence or coercive behaviours to control a woman’s reproductive choices. Perpetrators use various forms of RCA such as controlling the outcome of a pregnancy, contraceptive sabotage and pregnancy coercion. Current research has focused primarily on quantitative data and health interventions, yet there is limited qualitative research on the overall experience of RCA. To address this gap, this study aimed to investigate the question: “What are women’s lived experiences of RCA?”.MethodsTwenty women who had experienced RCA were recruited to participate in qualitative in-depth interviews. Data were analysed using interpretive phenomenological analysis.ResultsThree themes were developed that describe women’s lived experiences of RCA: I didn’t have a way out, where women described how their partners threatened them both with direct violence or indirectly through manipulation; I still feel guilty which centered around women’s overwhelming feelings of guilt and self blame and I don’t feel worthy, that outlined how RCA eroded women’s self-concept, particularly in relation to motherhood.ConclusionsOur findings foreground the profound impacts of RCA on women’s mental health, identity and wellbeing which can linger for many years after the experience. It is vital that practitioners working with women who have experienced RCA consider these impacts and how to address and respond to them effectively.